Phylogenomics reveals the slow-burning fuse of diatom evolution - Andrew J. Alverson; Wade R. Roberts; Elizabeth C. Ruck; Teofil Nakov; Matthew P. Ashworth; Karolina Bryłka; Kala M. Downey; J. Patrick Kociolek; Matthew Parks; Eveline Pinseel; Edward C. Theriot; Simon P. Tye; et al. (Proceedings of the National Academy of Sciences, 2025)
Evolution is often uneven in its pace and outcomes, with long periods of stasis interrupted by abrupt increases in morphological and ecological disparity. With thousands of gene histories, phylogenomics can uncover the genomic signatures of these broad macroevolutionary trends. Diatoms are a species-rich lineage of microeukaryotes that contribute greatly to the global cycling of carbon, oxygen, and silica, which they use to build elaborately structured cell walls. We combined fossil information with newly sequenced transcriptomes from 181 diverse diatom species to reconstruct the pattern, timing, and genomic context of major evolutionary transitions. Diatoms originated 270 Mya, and after >100 My of relative stasis in morphology and ecology, a radiation near the Jurassic–Cretaceous boundary led to the diversity of habitats and cell wall architectures characteristic of modern diatoms. This transition was marked by a genome duplication and high levels of gene tree discordance. However, short generation times increase the probability of coalescence between speciation events, minimizing the impacts of incomplete lineage sorting and implicating sequence saturation and gene tree error as the main sources of discordance. Nevertheless, a rigorous tree-based approach to ortholog selection resulted in strongly supported relationships, including some that were uncertain previously. Three pulses of accelerated speciation were detected, two of which were associated with the evolution of novel traits and ecological transitions. The first 100 My of diatom evolution was a slow-burning fuse that led to a burst of innovations in ecology, morphology, and life history that are hallmarks of contemporary diatom assemblages.